Public Accounting Research and Theories: A Literature Review - Zamzami, Faiz; Mukhlis, Mukhlis (Jurnal Ilmiah Akuntansi dan Bisnis, 2020)
The purpose of this study is to provide a structured overview of the literature on research on public accounting and the theories used by referring to articles published in four reputable international journals in 2009–2018. It is expected that this article can be a basis for future research and becomes a work request for more precise and focused research questions. A literature review-based approach with two important steps in the analysis of trends in public accounting research was used. First, journals as the source of the data are limited to four reputable international journals that published public sector research. Second, articles are divided into three areas that include financial accounting, management accounting, and auditing. A structured method was then used to analyze the relevant and identified articles. Results show that articles published in four leading international journals do not specifically discuss public accounting. So far, journals publishing public accounting remain rare. Of the four journals, articles in public reports are few. Ten popular theories on how to apply public accounting research were discussed. Keywords: Public Accounting, Literature Review, Theory.